An Age of Crisis Man and World in Eighteenth Century French Thought - Crocker, Lester G. (Johns Hopkins University Press, 2019)
Originally published in 1959. This book examines the French Enlightenment by analyzing critical thought in eighteenth-centruy France. It examines the philosophes' views on evil, free will and determinism, and human nature. This is an interesting group to look at, according to Crocker, because French Enlightenment thinkers straddled two vastly different time periods.